2022
DOI: 10.1016/j.aucc.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the construct and concurrent validity of the Richards-Campbell Sleep Questionnaire with intensive care unit patients and home sleepers

Abstract: Background: Sleep is vital to our wellbeing. Critically ill patients are vulnerable with effects of sleep deprivation including weakened immune function, decreased glucose tolerance, and increased sympathetic activity. Intensive care unit (ICU) patients' sleep evaluation is difficult and often not reliable. The most commonly used instrument for assessing ICU patients' perspective of their sleep, Richards-Campbell Sleep Questionnaire (RCSQ), has not been reported to have undergone known-group construct validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The median global RCSQ (54.4 [30.1, 77.1] mm) was somewhat higher than reported previously in some studies for example median 46 mm reported from a two‐centre study in Australia (Aitken et al, 2017), 47 mm from a one‐centre validation study in Germany (Krotsetis et al, 2017) and 44 mm from a one‐centre validation study in China (Chen et al, 2019) but lower than the median values (Ritmala‐Castren et al, 2017; Rood et al, 2019) and mean values for others (Kamdar et al, 2012; Richards et al, 2000). Of note, in our study scores for the RCSQ domain (VAS) ‘sleep depth’ were exceptionally low when compared to the results of other studies (Kamdar et al, 2012) but similar to others (Aitken et al, 2017; Ritmala‐Castren et al, 2021) indicating that self‐perceived sleep depth was low. These scores were particularly low for patients who classified their sleep as ‘poor’ or ‘very poor’ using the 5‐category scale.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The median global RCSQ (54.4 [30.1, 77.1] mm) was somewhat higher than reported previously in some studies for example median 46 mm reported from a two‐centre study in Australia (Aitken et al, 2017), 47 mm from a one‐centre validation study in Germany (Krotsetis et al, 2017) and 44 mm from a one‐centre validation study in China (Chen et al, 2019) but lower than the median values (Ritmala‐Castren et al, 2017; Rood et al, 2019) and mean values for others (Kamdar et al, 2012; Richards et al, 2000). Of note, in our study scores for the RCSQ domain (VAS) ‘sleep depth’ were exceptionally low when compared to the results of other studies (Kamdar et al, 2012) but similar to others (Aitken et al, 2017; Ritmala‐Castren et al, 2021) indicating that self‐perceived sleep depth was low. These scores were particularly low for patients who classified their sleep as ‘poor’ or ‘very poor’ using the 5‐category scale.…”
Section: Discussionsupporting
confidence: 87%
“…The overall sleep quality (global RCSQ score) was 76 (SD 13.5) mm (Ritmala-Castren et al, 2021). Therefore, the aim of this study was to determine the global RCSQ cut-off score for good to very good sleep during an ICU stay based on patients' verbal self-evaluation but also the utility of a simple 5-category item Likert scale in which patients rated their nocturnal sleep quality as 'very poor', 'poor', 'fair', 'good' and 'very good'. The study comprised a secondary (cohort) analysis of patient data from an interventional study in which the effectiveness of a sleep promotion bundle was tested (unpublished study).…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is a well-known phenomenon in sleep research, that a sleep dept can be developed in nights with disturbed sleep and a subsequent night with less disturbance -such as those at the normal ward after nights at the ICU -tend to be rated better than the following nights when no sleep debt is present [41]. Rating of sleep in the second night at the normal ward was comparable to results from intensive care units and rating of the sleep at home in the follow up was comparable to sleeping at home from other populations [42].…”
Section: Discussionmentioning
confidence: 68%
“…Adverse events including PONV, hypoxemia (de ned as a SpO 2 level < 95% with a need for oxygen supplementation) [8], postoperative ileus (de ned as an absence of atus or stools), urinary retention (de ned as the inability to void with bladder distention and need of catheterization), delirium (measured twice daily using the Confusion Assessment Method) [9] were recorded. Sleep quality during the rst postoperative night was evaluated using the Richards-Campbell Sleep Questionnaire [10]. Quality of life was assessed using the VAS score of the EuroQol 5 Dimension 5 Level (EQ-5D-5L) [11] 30 days after surgery by a telephone interview.…”
Section: Methodsmentioning
confidence: 99%